Differentiating the geographical origin of Ethiopian coffee using XRF- and ICP-based multi-element and stable isotope profiling. (30th August 2019) - Worku, Mohammed; Upadhayay, Hari Ram; Latruwe, Kris; Taylor, Alex; Blake, William; Vanhaecke, Frank; Duchateau, Luc; Boeckx, Pascal
Highlights: Consumer demand for single-origin specialty coffee increases the risk of fraudulent activities. Tracing of Ethiopian coffee origins is possible using multi-element and stable isotope profiling. XRF-based multi-elements with δ 13 C discriminated coffee origins with high classification accuracy. XRF technology is a promising tool for coffee profiling with the aim of authenticity detection. Abstract: To test the potential of different analytical tools to determine the geographical origin of Ethiopian coffee, 103 green arabica coffee samples from four coffee regions in Ethiopia were subjected to multi-elements and δ 13 C, δ 15 N and δ 18 O determinations. Multi-elements were determined by using inductively coupled plasma (ICP)- and X-ray fluorescence spectrometry (XRF)-based techniques, and δ 13 C, δ 15 N and δ 18 O were determined by using elemental analyzer-isotope ratio mass spectrometry. Using linear discriminant analysis, XRF-based multi-elements with and without δ 13 C appeared to be most effective in discriminating the geographical origin of coffee, giving higher classification accuracy (89 and 86%, respectively) than ICP-based multi-elements with and without stable isotopes (80%, each). These results demonstrate the potential of XRF-based multi-element profiling as a relatively fast and low-cost tool to trace the geographical origin of Ethiopian coffee. All together this study offers the proof of concept for a promising method that, upon standardization, could be used for coffee provenance authentication and fraud detection.